National strategy for the control of Fasciola gigantica in ruminant livestock - Kumar, Niranjan; Mishra, Anil Kumar (Indian Farming, 2025)
Fasciola gigantica, a liver fluke, is an important parasitic infection affecting ruminants in India. It has far-reaching consequences for the productivity of livestock, particularly in regions where environmental conditions favour lifecycle of the parasite. The economic burden of fascioliasis is immense, resulting in reduced meat and milk production, growth retardation in young animals, increased veterinary costs, and, in severe cases, death.This manuscript provides the insight on the current status of fascioliasis in India, identifies critical gaps in existing policies, and outlines recommendations for a comprehensive strategy to mitigate the impact of F. gigantica in ruminants.